2013
DOI: 10.1177/1358863x13496488
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the dimethylarginine dimethylaminohydrolase 1 gene (DDAH1) is related to asymmetric dimethylarginine (ADMA) levels, but not to endothelium-dependent vasodilation

Abstract: Objectives: Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthase. The breakdown of ADMA is mainly governed by the activity of dimethylarginine dimethylaminohydrolases (DDAHs). We investigated if genetic variation in the DDAH1 and DDAH2 genes were related to ADMA and l-arginine levels, as well as measures of endothelium-dependent vasodilation. Methods: In 1016 70-year-old participants of the population-based Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
6
2
1
Order By: Relevance
“…Our salient finding was a similar plasma level of ADMA in PPI users and non-users. This observation appears inconsistent with the previously reported ability of PPI to augment ADMA accumulation in vitro and in an animal model through a direct inhibition of DDAH-1 [ 1 ], an enzyme influencing circulating ADMA [ 16 , 17 , 18 , 19 ]. On the other hand, in subjects with a history of vascular disease, Ghebremariam et al [ 15 ] observed a more pronounced trend towards higher ADMA while on PPI compared to placebo in an interventional cross-over study, nevertheless the differences did not reach the statistical significance, which is in agreement with our cross-sectional retrospective analysis.…”
Section: Discussioncontrasting
confidence: 90%
“…Our salient finding was a similar plasma level of ADMA in PPI users and non-users. This observation appears inconsistent with the previously reported ability of PPI to augment ADMA accumulation in vitro and in an animal model through a direct inhibition of DDAH-1 [ 1 ], an enzyme influencing circulating ADMA [ 16 , 17 , 18 , 19 ]. On the other hand, in subjects with a history of vascular disease, Ghebremariam et al [ 15 ] observed a more pronounced trend towards higher ADMA while on PPI compared to placebo in an interventional cross-over study, nevertheless the differences did not reach the statistical significance, which is in agreement with our cross-sectional retrospective analysis.…”
Section: Discussioncontrasting
confidence: 90%
“…In 70-year-old Swedish participants in the Vasculature in Uppsala Seniors study (n = 1016), several DDAH1 SNPs were shown to be associated with ADMA levels (p <0.00005): rs11161606, rs12132677, rs13373844, rs233099, rs233109, rs376822qwoo7, rs11161614, rs12140935, rs3768226, rs527762, rs582145, rs6669293, rs669173, and rs7521189; no DDAH2 SNPs were significantly associated with ADMA levels. 39 In a study of 343 Australian patients with type 2 diabetes, the SNPs with the most highly significant association with ADMA levels were rs669173 (p = 2.96 × 10 −7 ; genotypic model), rs7521189 (p = 6.40 × 10 −7 ; additive model), rs2474123 (p = 0.00082; additive model), rs13373844 (p = 0.00027; dominant model), and rs986639 (p = 0.0015; genotypic model) in DDAH1 and rs3131383 (p = 0.0029; dominant model) in DDAH2. 40 In a combined analysis of the most strongly associated SNPs in DDAH1 and DDAH2 (rs669173 and rs3131383, respectively), there was a significant additive effect (p = 1.37 × 10 −8 ) on ADMA levels.…”
Section: Dimethylarginine Dimethylaminohydrolases 1 Andmentioning
confidence: 99%
“…Isoform 1 of DDAH is highly expressed in brain. Lind et al [58] showed that several polymorphisms in DDAH1 gene are related to ADMA level, but not to endothelium-dependent vasodilatation. Another group identified 4-nucleotide deletion/ insertion variant in the promoter region that leads to reduction of DDAH1 transcription activity and mRNA level, which increase the ADMA concentration and is a risk factor for thrombosis stroke and coronary heart disease [59].…”
Section: Genes Important For Homocysteine and Adma Metabolism And Antmentioning
confidence: 99%